Constructive Synergy: Beijing–Moscow No-Limits Partnership in Perspective - Long Zhao (China Quarterly of International Strategic Studies, 2022)
The ongoing Ukraine crisis and rising geopolitical tensions among great powers are creating a new security environment around China–Russia relations. The prediction of a China–Russia united front against the West is a misinterpretation of both countries’ history, their respective core interests, and distinct visions of world order. Beijing is unlikely to provide substantial military or financial aid to Moscow in its conflict with Ukraine where, apart from some foundational norms of international relations, few Chinese interests are at stake. Whereas some Western analysts lump together China and Russia in promoting the narrative of an epic struggle between democracy and autocracy, Beijing tries hard to immunize its relations with great powers against the fallout and repercussions of the Ukraine crisis and remains reluctant to engage with Moscow in ways that might create strong international backlash detrimental to its national interests. The growing proximity between China and Russia should rather be viewed as a countermeasure in response to the West’s concerted efforts to encircle and constrain rival powers than a strategic move to establish an anti-West sphere of interest.